THE IMPACT OF TAQWA ON ETHICS AND COMPETITIVE ADVANTAGE IN MALAYSIAN SMES - Mhd Sarif , Suhaimi; Ismail, Yusof (Online Journal of Islamic Management and Finance (OJIMF), 2024)
This paper investigates the influence of taqwa, an Islamic ethical framework, on the competitive advantage of small and medium-sized enterprises (SMEs) in Malaysia. Taqwa, embodying ethical conduct and responsibility, is posited as a key factor enhancing the competitive advantage of small businesses. The study aims to explore the impact of taqwa on ethics and competitive advantage of SMEs in Malaysia through personal interviews with five owners of SMEs. While previous studies have highlighted the crucial role of ethical and socially responsible practices in business success, the specific impact of taqwa in this context remains underexplored. This study addresses this gap by examining the role of taqwa in SMEs' strategies, ethical marketing, and resilience during challenging times, and employee well-being. The results of the study affirmed that taqwa has an impact on ethics into the structure of decision-making procedures. The impact of taqwa serves as a guiding principle for enterprises, ensuring that their activities conform to higher ethical standards while maintaining competitiveness. It also considers the implications of taqwa on entrepreneurial motivation, marketing orientation, and business sustainability.